2022
DOI: 10.1002/eap.2643
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for managing marine disease

Abstract: The incidence of emerging infectious diseases (EIDs) has increased in wildlife populations in recent years and is expected to continue to increase with global environmental change. Marine diseases are relatively understudied compared to terrestrial diseases but warrant parallel attention as they can disrupt ecosystems, cause economic loss, and threaten human livelihoods. While there are many existing tools to combat the direct and indirect consequences of EIDs, these management strategies are often insufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 228 publications
0
6
0
Order By: Relevance
“…Although this work is not yet completed after a decade of Bsal Task Force activities, the preparation for a Bsal invasion is far ahead of past experience with other amphibian-disease threats (Garner et al, 2016;Mendelson et al, 2019;Martel et al, 2020). The lessons learned we outline in this paper can serve as a model for other strategies to manage wildlife disease (e.g., marine wildlife disease: Glidden et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Although this work is not yet completed after a decade of Bsal Task Force activities, the preparation for a Bsal invasion is far ahead of past experience with other amphibian-disease threats (Garner et al, 2016;Mendelson et al, 2019;Martel et al, 2020). The lessons learned we outline in this paper can serve as a model for other strategies to manage wildlife disease (e.g., marine wildlife disease: Glidden et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, selective predation on infected prey does not always reduce infection prevalence ( Lopez & Duffy, 2021 ), and some models have shown that when the most heavily infected individuals in a population are culled, disease prevalence may increase due to persistence of less virulent strains of the parasite which are able to establish in sparser populations ( Bolzoni & De Leo, 2013 ; Behringer et al, 2020 ). Indeed, many authors do not consider culling an effective way to manage marine infectious diseases because of the dearth of knowledge on the relative importance of other environmental drivers and mechanisms of transmission and dispersion of pathogens in the ocean, and on the spatial scales at which infective stages and host larvae may travel (reviewed in Groner et al, 2016 ; Shields, 2018 ; Glidden et al, 2022 ). In the absence of this information, culling as a potential mechanism to manage the PaV1 disease remains contentious.…”
Section: Discussionmentioning
confidence: 99%
“…Culling diseased individuals during surveillance or fishing operations has also been suggested as a means to reduce disease transmission if the culled individuals are disposed of at land ( Behringer et al, 2012 ). However, whether culling is an efficient way to manage marine diseases is still a matter of debate ( Groner et al, 2016 ; Behringer et al, 2020 ; Glidden et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The successful mitigation and management of marine diseases are dependent, in part, on research that addresses our knowledge of microbial virulence and host‐pathogen interactions (Glidden et al., 2022 ; Groner et al., 2016 ). Here, we put forward three related questions, which, if addressed, would considerably advance our understanding of marine disease and pave the way for successful mitigation strategies to protect our oceans in the future.…”
Section: Introductionmentioning
confidence: 99%